Retrospective study of tetanus in 18 dogs—Causes, management, complications, and immunological status - Dörfelt, Stefanie; Mayer, Christine; Wolf, Georg; Straubinger, Reinhard K.; Fischer, Andrea; Hartmann, Katrin; Dörfelt, Rene (Frontiers in Veterinary Science, 2023)
Objective: Tetanus is a severe neurologic disease caused by Clostridium tetani, resulting in spastic paralysis. Canine tetanus is associated with serious complications such as aspiration and a high mortality rate of up to 50%. Material and Methods: Medical records of all dogs diagnosed with tetanus over 8 years (2014 – 2022) were analyzed for severity grade, treatment protocols, nutritional management, complications, as well as outcome, vaccination and antibody production in some dogs. No medical records were excluded. Normality was analyzed by the D’Agostino-Pearson test. Parametric, normally distributed data were presented as mean  standard deviation. Non-parametric, non-normally distributed data were presented as median (m) and range (minimum–maximum). The association between tetanus grade, progression of diseases, and duration of hospitalization were analyzed using the T-test, Mann-Whitney U test, and Kruskal-Wallis-test. A P-value ≤ 0.05 was considered significant. Results: Eighteen dogs were identified. Most affected dogs were classified into severity grade II (66.7%, 12/18). Clinical signs deteriorated in 55.6% of dogs (10/18). In 88.9% of dogs (16/18), a source was identified. Nine dogs required surgical wound revision. A percutaneous endoscopic gastropexy tube was placed in 83.3% of dogs (15/18) for nutritional support. Medical treatment included metronidazole, methocarbamol, and combinations of different sedatives adapted to the patient’s requirements. Tetanus antitoxin was used in 72.2% of dogs (13/18) without reported adverse events in all. The survival rate was 88.9% (16/18). Complications, such as hypertension, aspiration pneumonia, and laryngeal spasm occurred in 12/18 dogs. Median hospitalization time (8 days; range 0 – 16 days) was associated with the maximum tetanus severity grade (p = 0.022). Rapid eye movement behavior disorder was observed in 72.2% of dogs (13/18). In five dogs, antibodies were measured after recovery and in 4/5 dogs no antibodies were detectable despite generalized tetanus disease. Vaccination with tetanus toxoid was performed in five dogs following the disease. Conclusion: In the present study, the mortality rate was lower than previously reported. Tetanus is still a life-threatening disease, but the prognosis may be good if adequate management and monitoring can be ensured.